Maine's Science and Engineering Brain Drain: How Much and Why? - Tornatzky, Louis; Gray, Denis; Tarant, Stephanie; Howe, Julie (Maine Policy Review, 1998)
More than the traditional economic ingredients, the new global economy is being built around talented people with special knowledge and skills, those with the capacity to innovate and the entrepreneurial wherewithal to turn ideas into commercial products. Hence many states are shifting economic development strategies away from efforts that market commodities such as low tax rates and cheap labor, and toward efforts that amass and equip talented people with the tools of innovation. In short, states are beginning to think about strategies for recruiting and/or retaining talented workers. In this regard, the Southern Technology Council conducted a national study to compare states on their performance in retaining their own recent science and engineering graduates and/or attracting similar graduates from states elsewhere in the country. "How is Maine doing?" they ask. In a word, poorly. The authors compare Maine to other states on a number of performance indicators and predictor variables to assess why this is so. They suggest Maine take bold steps now to prevent the continued loss of its most important commodity of the future.
Keywords: Maine; brain drain; labor force